Endometrial scratch vs no intervention in egg donation cycles: the ENDOSCRATCH trial protocol - Alexandra Izquierdo; Laura de la Fuente; Katharina Spies; Jennifer Rayward; Lourdes López; David Lora; Alberto Galindo (BMC, 2020)
Abstract Background The effects of endometrial scratching (ES) on embryo implantation have been studied for many years. Several studies have shown better outcomes when performed on patients undergoing intrauterine insemination and in vitro fertilization (IVF) cycles, but many other reports have not been able to find these differences. As far as cycles with donor eggs are concerned, reported evidence is scarce. Our aim in this trial is to determine if ES is useful for those patients undergoing IVF cycles with donor eggs, in order to assure a greater homogeneity in embryo quality and endometrial preparation. Methods This single centre randomized controlled trial will include patients undergoing an egg donation cycle, meeting the inclusion criteria and who accept to participate in the study. Once informed consent is signed, patients will be randomly allocated to the study arm (group A) and then receive ES in the luteal phase of the cycle prior to embryo transfer, or the control arm (group B) without any intervention. All cycle data will be collected and analyzed to obtain the clinical pregnancy and the live birth rates in the two groups. Discussion Several studies have tried to determine the effectiveness of an ES in IVF cycles, but it is still unclear due to the heterogeneity of these reports. The aim of this study is to determine if there are differences in clinical pregnancy rate and live birth rate in egg donor cycles, when comparing an ES performed in the preceding luteal phase versus no intervention, given that embryo quality and endometrial preparation protocols will be comparable. Trial registration Ethical approval of version 2.0 of this trial was obtained on the 13th January 2017. It was retrospectively registered on the 5th April 2017 as the ENDOSCRATCH Trial ( NCT03108157 ) in ClinicalTrials.gov.